Elevational turnover in the composition of leaf miners and their interactions with host plants in Australian subtropical rainforest. (25th February 2016) - Maunsell, Sarah C.; Burwell, Chris J.; Morris, Rebecca J.; McDonald, William J. F.; Edwards, Edward D.; Oberprieler, Rolf G.; Kitching, Roger L.
Abstract: Leaf miners are specialist herbivorous insects that are potentially vulnerable to environmental change because of their dependency on particular host plants. Little, however, is known about how climate affects the distribution of leaf miner communities and their interactions with host plants. Elevational gradients are useful tools for understanding how ecological communities respond to local clines in climate. Given that plant communities are known to undergo elevational turnover in response to changes in climatic conditions, we expect that leaf miner species will also change with elevation. We repeatedly hand collected leaf miners along three elevational gradients in subtropical rainforest in eastern Australia. Individual leaf miners were counted and identified to species, and their host plants were recorded. We tested if leaf miner species richness and the number of unique interactions among leaf miner and host plant species were affected by elevation. We also tested if the composition of leaf miner species and the composition of interactions between leaf miners and host plants showed a relationship with elevation. The rarefied number of unique leaf miner–host plant interactions significantly decreased with elevation, with a slight peak at approx. 700 m a.s.l., while neither rarefied or observed species richness (species density) of leaf miners nor observed numbers of unique interactions (interaction density) were significantly affected by elevation. The composition of leaf miner species and the composition of leaf miner–host plant interactions (occurrence of pairwise interactions) were significantly related to elevation. Elevational turnover in leaf miner species composition indicated that different species varied in their response to changes in biotic and/or abiotic conditions imposed by increasing elevation. Through our analyses, we identified four leaf miner species that may be locally vulnerable to climate change, as a result of their restricted elevational distribution and level of host specificity.